A new species of Stilestrongylus (Nematoda, Heligmonellidae) from the Atlantic Forest of Misiones, Argentina, parasitic in Euryoryzomys russatus (Cricetidae, Sigmodontinae) - Panisse, Guillermo (2018)
A new species of Heligmonellidae (Trichostrongylina, Heligmosomoidea), Stilestrongylus kaaguyporai n. sp. is described from the small intestine of Euryoryzomys russatus (Rodentia, Cricetidae, Sigmodontinae) from the Argentine Atlantic Forest, in the Misiones province. The new species was found at Campo Anexo Manuel Belgrano, Reserva de Vida Silvestre Urugua-í and Parque Provincial Urugua-í, with a prevalence of 73% in 15 hosts examined. Stilestrongylus includes 24 Neotropical species, all parasitic in rodents, mostly Sigmodontinae. Stilestrongylus kaaguyporai n. sp. can be differentiated from its congeners by the following characters: caudal bursa dissymmetrical with right lobe larger and pattern of type1–4 in both lobes, rays 6 not forming a lateral trident with rays 4 and 5, rays 8 with dissymmetrical pathway, genital cone hypertrophied with a conspicuous hood-like projection and females with a marked dorso-ventral torsion of the posterior end. This report is the second record of a Stilestrongylus species in E. russatus, increasing to nine the number of parasitic species known from this host.